儒學、還是儒學自由主義？: Confucianism or Confucian Liberalism? - FAN, Ruiping (International Journal of Chinese & Comparative Philosophy of Medicine, 2018)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. In providing his reasons for not objecting to the legalization of same-sex marriage, Professor Fang Xudong fully accepts a robust liberal dichotomy between the right and the good as well as the liberal principle of neutrality. This renders his Confucian reflection essentially liberal rather than authentically Confucian. It is ethically incoherent for him to claim that he does not object to the legalization of same-sex marriage although he believes same-sex couples cannot embody ethical integrity as heterosexual marriages do. DOWNLOAD HISTORY | This article has been downloaded 79 times in Digital Commons before migrating into this platform.